Preparation of Bacterial Cellulose Using Enzymatic Hydrolysate of Olive Pomace as Carbon Source - Ceren Sagdic-Oztan; Andreas Koschella; Thomas Heinze; Nevin Gul-Karaguler; Melek Tuter (BioResources, 2023)
Bacterial cellulose has superior physical and chemical properties, biocompatibility, and purity. However, the high production cost obstructs the common use of this polymer. This study investigated the efficiency of olive pomace, an important by-product of olive oil industry in Turkey, as a carbon source for Novacetimonas hansenii. Olive pomace pretreatment with 1% H3PO4 was followed by enzymatic hydrolysis. The maximal reducing sugar concentration upon enzymatic process was 9.3 g/L with 1 enzyme: 6 substrate (dry matter) ratio. After incubation in the growth media prepared with the obtained reducing sugar as carbon source, the highest bacterial cellulose production was 0.68 g/L. Structural analysis indicated that bacterial cellulose from the enzymatic media and the conventional Hestrin-Schramm medium possess similar characteristics. The present work provides a favourable method to reduce the cost of bacterial cellulose production.